2021 23rd European Microelectronics and Packaging Conference &Amp; Exhibition (EMPC) 2021
DOI: 10.23919/empc53418.2021.9585007
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature Metal Bonding for Optical Device Packaging

Abstract: Low-temperature solid-liquid interdiffusion (SLID) bonding is an attractive alternative for the packaging of optical devices. It reduces global residual stress build up caused by differences in coefficient of thermal expansion (CTE) at elevated temperatures. This work applied the Cu-Sn-In-based SLID bonding method to bond silicon and optically transparent materials at 200 °C. Experimental results show a successful bonding with minor unavoidable misalignment from the CTE mismatch and major misalignment from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…However, when the bonding temperature is ≤200°C the bond is composed of single phase Cu 6 (Sn,In) 5 , which doesn't transform to Cu 3 (Sn,In) even after extensive solid state annealing (>500h at 150°C) (3). In order to demonstrate that small µ-bonds can be manufactured at temperatures as low as 150°C Si wafers containing 10 µm-sized microbumps based on the Cu-Sn-In ternary system were fabricated with wafer-level bonding (5,6). The test wafers had symmetrical metallization structure of 4 µm Cu| 1,5 µm Sn|1,5 µm In.…”
Section: Auin Bondingmentioning
confidence: 99%
“…However, when the bonding temperature is ≤200°C the bond is composed of single phase Cu 6 (Sn,In) 5 , which doesn't transform to Cu 3 (Sn,In) even after extensive solid state annealing (>500h at 150°C) (3). In order to demonstrate that small µ-bonds can be manufactured at temperatures as low as 150°C Si wafers containing 10 µm-sized microbumps based on the Cu-Sn-In ternary system were fabricated with wafer-level bonding (5,6). The test wafers had symmetrical metallization structure of 4 µm Cu| 1,5 µm Sn|1,5 µm In.…”
Section: Auin Bondingmentioning
confidence: 99%
“…With excellent wetting properties on glass, quartz, and ceramic materials, they could be ideal for metal-to-non-metal joining [30]. Furthermore, the bonding temperature can be as low as 150 °C [34], and the remelting temperature exceeds 600 °C [21], as the bonding results in a fully formed IMC bond-line without any traces of unreacted low melting point material [34], [35], [36]. Two IMCs (Cu3(In,Sn) and Cu6(In,Sn)5) have been reported to form in reactions of InSn alloys with Cu at temperatures between 150 °C and 400 °C [37].…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the bonding temperature impacts the reaction products and the number of de-fects: 1) Cu3Sn phase and Cu6(Sn,In)5 with several voids at Cu3Sn/Cu interface at a bonding temperature of 250°C, and 2) void-free single Cu6(Sn,In)5 at 150°C and 170°C. O. Golim et al [20] bonded Si wafer to different optically transparent mate-rials at 200°C. The bond was composed of the single Cu6(Sn,In)5 phase.…”
Section: Introductionmentioning
confidence: 99%